(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2020)
The accurate estimation of time since death sometimes is very important for forensic experts in administration of justice. Various cells and tissues of the body showed significant changes with respect to post-mortem interval and one such sample is blood. The aim of this study is to assess the post-mortem autolytic changes in morphology of red blood cells and haemogram pattern for estimation of time since death. The present study was a cross sectional one and non random purposive sampling was done. The blood samples from 60 dead bodies which were brought for postmortem examination in the mortuary and preserved in <4oC temperature was taken after taking into consideration inclusion and exclusion criteria. The time since death was recorded and studied with respect to autolytic changes in RBC morphology and haemogram pattern. On meticulous examination of all the blood samples there were certain changes observed in the RBCs shape, intactness, central pallor and peripheral redness with respect to post-mortem interval. However, no statistical significance was correlated in the haemogram (RBC count, Hemoglobin, haematocrit, MCV, MCH and MCHC) with respect to time since death.